East and West in Harmony: A Comparative Study of Arabic and English Proverbs - Omar Mohammad-Ameen Ahmad Hazaymeh (Comparative Literature: East & West)
This paper presents a contrastive review of similar proverbs in Arabic and English, aiming to explore cultural and linguistic nuances within each language. The objective is to identify shared wisdom, values, and social insights while highlighting differences in cultural contexts that shape these expressions. Through a qualitative analysis of selected proverbs, the study investigates their meanings, usage, and implications in daily communication. Findings indicate that while many proverbs in both languages convey parallel messages, subtle variances arise due to cultural, historical, and social factors unique to each. These findings suggest that proverbs reflect deeper societal attitudes and traditions, and their interpretation is context-dependent. The paper recommends further cross-cultural studies on proverbs to enhance understanding of linguistic diversity. In conclusion, this study underscores the importance of proverbs as cultural artifacts, offering insight into both the universal and specific human experience across Arabic and English.